Peran perpustakaan daerah dalam pengembangan minat baca di masyarakat - Habiba Noer Maulida (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2015)
This paper discusses the role of public region libraries that very strategic in enhancing the quality of life, as a vehicle for lifelong learning to develop the potential of people to become religious and pious, noble, healthy, knowledgeable, capable, creative, independent, and become citizens of a democratic and is responsible in mendudkung of national education, and is a vehicle for the preservation of the cultural wealth of the nation, according to what has been mandated by the Act of 1945 is as a vehicle for educating the nation.This paper discusses the role of public region libraries that very strategic in enhancing the quality of life, as a vehicle for lifelong learning to develop the potential of people to become religious and pious, noble, healthy, knowledgeable, capable, creative, independent, and become citizens of a democratic and is responsible in mendudkung of national education, and is a vehicle for the preservation of the cultural wealth of the nation, according to what has been mandated by the Act of 1945 is as a vehicle for educating the nation. <w:LsdExc